Seasonal Incidence And Histopathologic Study Of Protozoan Infestation In Clarias Sp., Collected From A Local Fish Market Of Kolkata, West Bengal (India) (Applied Biological Research, 2022)
Protozoans exhibit highly diverse ecological inter-relationship and most  complicated host-relationship. The catfish Clarias sp. is important  component in human diet in many countries especially those in tropical and  subtropical areas where malnutrition is a major problem. Clarias sp. (size  20-22 cm, weight 80-90 g) were collected from a local fish market of  Kolkata (India) during pre-monsoon, monsoon and post-monsoon seasons of 2017-2019. The blood, gill and skin of catfish were examined in  laboratory for protozoan parasites and routine histopathological study of  selected tissues was performed. Photo-documentation was done using microscope-fitted with digital camera. The study revealed that the intensity  of infection was more in ciliate parasites, and the fish had marked lesions in  gills and skin. The highest parasitic infection was observed in post-monsoon  season i.e. from November to Februaryfollowed by pre-monsoon period;  while the lowest infection was noted in monsoon season i.e. from July to  October. The study revealed that the environmental factors are responsible  for spreading infection.
Keywords: Catfish; gill; protozoa; skin